Improvement of the Method for Calculating the Metal Temperature Loss on a Coilbox Unit at The Rolling on Hot Strip Mills - Kukhar, Volodymyr; Kurpe, Oleksandr; Klimov, Eduard; Balalayeva, Elena; Dragobetskii, Vladimir (International Journal of Engineering and Technology, 2018)
The paper improves the calculation methodology of metal temperature loss during hot rolling process at continuous mills. The proposed methodology can be implemented at hot strip mills with various in-line equipment arrangements within the temperature ranges appropriate for processes simulation of hot rolling, normalized rolling and Thermo-Mechanical Control Process of carbon and microalloyed steels. It provides engineering analysis of unaccounted temperature losses of feed by means of radiation and convection, which, in the first time, through the time factor, additionally accounts for strip motion speed factors, roller table length and feed length, and also length of rolls contact arc with metal. The accountability of the above mentioned factors in the various compositions depending on the rolling method increases the engineering simulation accuracy, ensures the versatility of the elaborated method with respect to different types of mills and makes the scientific novelty of the study. The equations were developed to calculate the metal temperature loss while coiling at the CoilBox unit. The equations accounts for the influence on the temperature of strip length, coiling and uncoiling speed, strip thickness, inside radius of the reeling coil, the time the feed rests being coiled. The improved model was verified based on actual data. Â